Ekologi Sastra dalam Mitos Panastan di Desa Adat Penestanan Ubud - Dian Saputra, I Made; Indrawan Jendra, Made Iwan; Putu Intan Adelia Ananda Putri; Kartika Sari, Ni Ketut Tirta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Abstract This research, entitled